Curcuphenols facilitate the immune driven attenuation of metastatic tumour growth - Ellis, Samantha L. S.; Nohara, Lilian L.; Dada, Sarah; Saranchova, Iryna; Munro, Lonna; Choi, Kyung Bok; Garrovillas, Emmanuel; Pfeifer, Cheryl G.; Williams, David E.; Cheng, Ping; Andersen, Raymond J.; Jefferies, Wilfred A. (Frontiers in Natural Products, 2023)
One of the primary obstacles in current cancer treatments lies in the extensive heterogeneity of genetic and epigenetic changes present in tumours. However, there also remains the additional impediment that certain types of cancer exhibit shared deficiencies in the antigen processing machinery (APM), including the downregulation of human leukocyte antigen (HLA) class I molecules resulting in immune escape in metastatic disease. Notably, current cell-based immunotherapies primarily focusing on T lymphocytes and immune checkpoint inhibitors have largely overlooked the crucial task of reversing immune escape. This oversight might explain the limited success of these approaches as effective cancer immunotherapies. Hence, there is a critical 3 need to prioritize the discovery of new therapeutic candidates that can effectively address immune escape and synergize with evolving immunotherapy strategies. In this context, we identified curcuphenol in a cell-based screen from a library of marine extracts as a chemical entity that reverses the immune-escape phenotype of metastatic cancers. This study describes the synthesis of analogues by informed design of naturally occurring curcuphenol with enhanced chemical properties and biological efficacy. Here we test the hypothesis that these curcuphenol analogues can evoke the power of the immune system to reduce the growth of metastatic disease in tumour bearing animals. Our findings indicate that these compounds effectively restore the expression of APM genes in metastatic tumours and inhibit the growth of highly invasive tumours in preclinical models, thereby counteracting the common immune evasion phenomenon observed in metastatic cancers. Combination cancer immunotherapies capable of boosting APM expression, hold great potential in maximizing the effectiveness of immune blockade inhibitors and eradicating invasive tumours.